Client Group Activism and Student Moral Development in Clinical Legal Education - Adrian Evans (Legal Education Review)
In 2015, the Harmful Digital Communication Act (HDCA or “Act”) was enacted with the aim of eliminating harm caused by digital communications. After a year of being partially in force there have been a relatively large number of cases under section 22 of the Act. Anyone over the age of 14 can potentially face sanctions; the first person to be convicted under the Act was an 18 year old. This paper highlights the need for young people to be aware of, and engaged with, their legal rights and obligations, and presents “Privacy Games” (www.privacygame.com), an online game that uses intuitive, image based online scenarios to teach adolescents about privacy and online safety.